Effect of Probiotic on Some Physiological Parameters in Broiler Breeders - Sultan, Khalid H.; Abdul-Rahman, Saeb Y. (International Journal of Poultry Science, 2011)
The study was conducted to evaluate the effect of probiotic diet supplementation on some physiological parameters in Broiler Breeders. 30 Cobb Breeder hens were used (46 week aged), divided into 3 groups (10 hens each). The 1st group was reared on standard ration (control), the 2nd and the 3rd groups were given 10 and 20 gm of probiotic/kg ration for 4 weeks. The results revealed that the probiotic treatment causes a significant increase in LH and FSH serum levels (3rd group) and in T3 levels in (2nd and 3rd group) as compared with control group at p